The Effect of Short Story Towards Students’ Speaking Ability at Grade XI IPA1 of SMA Negeri 1 Anggaberi - Umar, Umar; Sachrin, Rini Oktavyani (Indonesian Research Journal on Education, 2024)
This research investigated the effect of short story towards students’ speaking ability at grade XI IPA1 of SMA Negeri 1 Anggaberi. This research applied pre-experimental design by using one class; pretest and posttest design. The sample of this research was 20 students. The sample was taken by using purposive sampling. The data was analyzed by using descriptive statistics and inferential statistics analysis. The finding shows there is any significant effect of short story in increasing students’ speaking ability at grade XI IPA1 of SMA Negeri 1 Anggaberi. The calculation result showed that  t-test was 14  and t-table was 1,729 (df=19, α=0,05), it means that hypothesis of this research was accepted or there is significant effect on students’ speaking ability after teaching by using short story at grade XI IPA1 of SMA Negeri 1 Anggaberi.